Flow investigation of cross-flow turbine using CFD method. Issue 1 (December 2020) - Aditya Sardjono, Joshua; Darmawan, Steven; Tanujaya, Harto
Abstract: Cross-flow turbine is one of prime mover type that is simple, capable to extract water power and easy to be manufactured. The runner is working at 2 stages. The need of high momentum has lead researchers to design water nozzle, blades, as well as the set-up between nozzle and runner. High momentum water nozzle and cross-flow runner has been designed individually with the same design criteria. Unfortunately, experimental testing may not gain specific flow pattern inside the nozzle and the runner. The purpose of this study is to investigate the flow pattern inside the nozzle, runner using CFD method, Ansys 2019 R3 academic version. The CFD simulation done 3-dimensionally with 5 nozzle inlet velocity variations: 2 m/s, 3 m/s, 4 m/s, 5 m/s and 6, 487 m/s. The fluid is assumed to be 1 phase, using mesh with 17.750 nodes, inlet fluid pressure 1, 05 Pa, and temperature 24, 85°C. The results showed that the lowest velocity and pressure for variation 1 at 1 st stage (v1) = 6, 65 m/s and (p1) = -11931, 5 Pa, and the highest velocity and pressure at 1 st stage (v5) = 21, 72 m/s and (p5) = -127521 Pa. At 2 nd stage, variation 1 and 5 resulting velocity (v1) = 1, 78 m/s and (p1) 593, 264 Pa, (v5) = 5, 83 m/s and (p5) = 6360, 32 Pa respectively. The main different of the flow pattern between 5 inlet velocity variations is the final flow thickness inside the runner get thicker at higher velocity, which is assumed to gain more rotational velocity.